Deferiprone protects the isolated atria from cardiotoxicity induced by doxorubicin - Xu Ling-jie; Jin Liang; Pan Hong; Zhang Ao-zhen; Wei Gang; Li Ping-ping; Lu Wei-yue (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of deferiprone on doxorubicin-induced cardiotoxicity and determine its protection on cardiac contractility in vivo at tissue level. Methods: Spontaneously-beating isolated atria from rats were pre-treated with deferiprone for 10 min at 1.2 mmol/L or 0.3 mmol/L, respectively before co-incubation with doxorubicin (DOX) at 0.03 mmol/L for 60 min. Contractility (dF/dt) was assessed every 10 min during the incubation. After that, the tissues around the sinuatrial nodes were fixed for ultrastructural study; succinate dehydrogenase (SDH) and Cu, Zn superoxide dismutase (Cu, Zn-SOD) activity, as well as malondialdehyde (MDA) level of the atria were assayed. Results: Treatment with DOX alone resulted in a 49.34% reduction of the contractility, mitochondria swelling, disruption of mitochondrial crista and decreased electron density of the matrices. Conversely, with the presence of deferiprone, the negative inotropic effect and lesions in the cardiac mitochondria structure induced by DOX were attenuated. Cu, Zn-SOD activity increased by 12.97%–12.11%, the MDA level decreased by 29.12%–39.82% and succinate dehydrogenase (SDH) activity was ameliorated by 25.15%–34.76%. Conclusion: Deferiprone can efficiently preserve cardiac contractility. Moreover, the results of this study indicate that deferiprone is able to protect mitochondrial function and structure form damage induced by DOX. This cardiac protective potential of deferiprone could be due to its defense capability against oxidative damage.